HARVESTING UTERINE NEUTROPHILS IN BUFFALOES BY ASPIRATIOIN AND LAVAGE TECHNIQUES - BABU, K RAMESH; KRISHNA, K MOULI; PADMAJA, K (The Indian Journal of Animal Reproduction, 2011)
Sixty five graded Murrah buffaloes were divided into group I (control) and group II (Infertile) and subjected to aspiration technique at day O and lavage at day 4 of the cycle for harvesting uterine neutrophils. Sampling at day 0 of the cycle by aspiration technique yielded cells in 92.3% cases (60/65). Whereas, 96.93% (63/65) samples provided cellular fraction, when buffaloes were lavaged at day 4 of the cycle. The mean neutrophils counts in smears obtained at day O were 4.6 ± 0.64 and 45.69 ± 3.88% in group I and II, respectively. Where as at day 4 of the cycle, the counts were 5.6 ± 0.78 and 57.82 ± 3.50% in group I and II, respectively.